Pharmacology and drug interactions of cannabinoids. (3rd March 2020) - Landmark, Cecilie Johannessen; Brandl, Ulrich
ABSTRACT: Cannabinoids include a variety of substances, of which cannabidiol (CBD) is the main substance investigated for the treatment of epilepsy, and this will be the focus in the present review. CBD preparations exist in various forms. There are significant differences in quality control regarding content and reproducibility for an approved drug versus herbal preparations. Cannabidiol has challenging pharmacological properties, and pharmaceutical and pharmacokinetic aspects will depend on the formulation or preparation of a certain product. This article will focus on the characteristics, pharmacokinetic challenges, and interactions of standardised CBD‐containing drugs based on evidence from clinical and pharmacokinetic studies.